chaining multi-parameter functions - function

Suppose I have two functions, f:X->Y and g:Y*Y->Z.
I want to make a third function, h(a, b) = g(f(a), f(b)).
h a b = g (f a) (f b)
Is there any way to write it like h(a, b) = g*f (a, b)?
And what if h(a,b,c,d) = g2*g1*f2*f1 (a,b,c,d), where g_i takes 2 args?

Searching Hoogle for functions with the right signature reveals on from Data.Function. According to its documentation,
g `on` f
seems to be what you want.

The on combinator (in Data.Function, as pointed out by gspr in another answer) is defined by
g `on` f = \x y -> g (f x) (f y)
Which would allow you to write
h = g `on` f
You can make higher-dimensional generalizations of this, for example
g `on3` f = \x y z -> g (f x) (f y) (f z)
g `on4` f = \w x y z -> g (f w) (f x) (f y) (f z)
So that you could write
h = g `on3` f
There may be a way to write on3 and on4 in terms of on, but if there is I can't see it at the moment.

You may also find Arrows interesting. Here's one way to do it:
h g f a b = uncurry g ((f *** f) (a, b))
Which is equivalent to your example (except that g and f are not free) and on. Using:
definition of *** for functions:
(***) f g ~(x,y) = (f x, g y)
definition of uncurry:
uncurry f p = f (fst p) (snd p)
And substituting them into the original equation:
h g f a b = uncurry g (f a, f b) (used *** definition)
h g f a b = g (f a) (f b) (used uncurry definition)

Related

How to define a function based on its type?

I'm trying to define a simple Haskell function with the type (m -> n -> l) -> (m -> n) -> m -> l.
I thought that it needs be to defined as f g h x = f g (h x), but apparently that's not true. How could I correct this function?
Based on the signature, the only sensical implementation is:
f :: (m -> n -> l) -> (m -> n) -> m -> l
f g h x = g x (h x)
This makes sense since we are given two functions g :: m -> n -> l and h :: m -> n, and a value x :: m. We should construct a value with type l. The only way to do this is to make use of the function g. For the parameter with type m we can work with x, for the second parameter we need a value of type n, we do not have such value, but we can construct one by applying h on x. Since h x has type h x :: n, we thus can use this as second parameter for g.
This function is already defined: it is a special case of (<*>) :: Applicative f => f (n -> l) -> f n -> f l with f ~ (->) m.
Djinn is a tool that reasons about types and thus is generating function definitions based on its signature. If one queries with f :: (m -> n -> l) -> (m -> n) -> m -> l, we get:
f :: (m -> n -> l) -> (m -> n) -> m -> l
f a b c = a c (b c)
which is the same function (except that it uses other variable names).
f :: (m -> n -> l) -> (m -> n) -> m -> l
f g h x = _
Now you need to use the arguments in some way.
g (_ :: m) (_ :: n) :: l
h (_ :: m) :: n
x :: m
Both g and h need a value of type m as their first argument. Well, luckily we have exactly one such value, so it's easy to see what to do.
g x (_ :: n) :: l
h x :: n
x :: m
So now g still needs a value of type n. Again we're lucky, because applying h to x has produced such a value.
g x (h x) :: l
h x :: n
x :: m
Ok, and there we now have something of type l, which is what we needed!
f g h x = g x (h x)
f :: (m -> n -> l) -> (m -> n) -> m -> l
f g h x = l
where
l =
what can produce an l for us? only g:
g
which takes two parameters, an m and an n,
m n
but where can we get those? Well, m we've already got,
m = x
and n we can get from h,
n = h
which needs an m
m
and where do we get an m? We've already got an m!

In Haskell how to "apply" functions in nested context to a value in context?

nestedApply :: (Applicative f, Applicative g) => g (f (a -> b)) -> f a -> g (f b)
As the type indicates, how to get that (a->b) applied to that a in the context f?
Thanks for help.
This one of those cases where it's helpful to focus on types. I will try to keep it simple and explain the reasoning.
Let's start with describing the task. We have gfab :: g(f(a->b)) and fa :: f a, and we want to have g(f b).
gfab :: g (f (a -> b))
fa :: f a
??1 :: g (f b)
Since g is a functor, to obtain type g T we can start with a value ??2 of type g U and apply fmap to ??3 :: U -> T. In our case, we have T = f b, so we are looking for:
gfab :: g (f (a -> b))
fa :: f a
??2 :: g U
??3 :: U -> f b
??1 = fmap ??3 ??2 :: g (f b)
Now, it looks like we should pick ??2 = gfab. After all,that's the only value of type g Something we have. We obtain U = f (a -> b).
gfab :: g (f (a -> b))
fa :: f a
??3 :: f (a -> b) -> f b
??1 = fmap ??3 gfab :: g (f b)
Let's make ??3 into a lambda, \ (x :: f (a->b)) -> ??4 with ??4 :: f b. (The type of x can be omitted, but I decided to add it to explain what's going on)
gfab :: g (f (a -> b))
fa :: f a
??4 :: f b
??1 = fmap (\ (x :: f (a->b)) -> ??4) gfab :: g (f b)
How to craft ??4. Well, we have values of types f (a->b) and f a, so we can <*> those to get f b. We finally obtain:
gfab :: g (f (a -> b))
fa :: f a
??1 = fmap (\ (x :: f (a->b)) -> x <*> fa) gfab :: g (f b)
We can simplyfy that into:
nestedApply gfab fa = fmap (<*> fa) gfab
Now, this is not the most elegant way to do it, but understanding the process is important.
With
nestedApply :: (Applicative f, Applicative g)
=> g (f (a -> b))
-> f a
-> g (f b )
to get that (a->b) applied to that a in the context f, we need to operate in the context g.
And that's just fmap.
It's clearer with the flipped signature, focusing on its last part
flip nestedApply :: (Applicative f, Applicative g)
=> f a
-> g (f (a -> b)) --- from here
-> g (f b ) --- to here
So what we have here is
nestedApply gffun fx = fmap (bar fx) gffun
with bar fx being applied under the g wraps by fmap for us. Which is
bar fx :: f (a -> b)
-> f b
i.e.
bar :: f a
-> f (a -> b)
-> f b
and this is just <*> isn't it, again flipped. Thus we get the answer,
nestedApply gffun fx = fmap (<*> fx) gffun
As we can see only fmap capabilities of g are used, so we only need
nestedApply :: (Applicative f, Functor g) => ...
in the type signature.
It's easy when writing it on a sheet of paper, in 2D. Which we imitate here with the wild indentation to get that vertical alignment.
Yes we the humans learned to write first, on paper, and to type on a typewriter, much later. The last generation or two were forced into linear typing by the contemporary devices since the young age but now the scribbling and talking (and gesturing and pointing) will hopefully be taking over yet again. Inventive input modes will eventually include 3D workflows and that will be a definite advancement. 1D bad, 2D good, 3D even better. For instance many category theory diagrams are much easier to follow (and at least imagine) when drawn in 3D. The rule of thumb is, it should be easy, not hard. If it's too busy, it probably needs another dimension.
Just playing connect the wires under the wraps. A few self-evident diagrams, and it's done.
Here's some type mandalas for you (again, flipped):
-- <$> -- <*> -- =<<
f a f a f a
(a -> b) f (a -> b) (a -> f b)
f b f b f ( f b) -- fmapped, and
f b -- joined
and of course the mother of all applications,
-- $
a
a -> b
b
a.k.a. Modus Ponens (yes, also flipped).

Haskell function composition - two one-dimensional functions to a two dimensional function

Let's assume I have a function f in Haskell, It takes a Double and returns a Double, and I have function g that also takes a Double and returns a Double.
Now, I can apply f to g like this: f . g.
Now, let's take a higher-dimensional function f, that
takes two Doubles and outputs one:
f :: Double -> Double -> Double
or
f :: (Double, Double) -> Double
And I have two g functions as well:
g1 :: Double -> Double, g2 :: Double -> Double
Now, I want to compose the functions to get something like:
composition x = f (g1 x) (g2 x)
Can this be achieved just by using the dot (.) operator?
You can make use of liftA2 :: Applicative f => (a -> b -> c) -> f a -> f b -> f c for this:
composition = liftA2 f g1 g2
Since a function is an applicative [src]:
instance Applicative ((->) r) where
pure = const
(<*>) f g x = f x (g x)
liftA2 q f g x = q (f x) (g x)
and liftA2 is implemented as [src]:
liftA2 :: (a -> b -> c) -> f a -> f b -> f c
liftA2 f x = (<*>) (fmap f x)
this will thus be resolved to:
liftA2 f g1 g2 x = (<*>) (fmap f g1) g2 x
= (fmap f g1 <*> g2) x
= (f . g1 <*> g2) x
= (\fa ga xa -> fa xa (ga xa)) (f . g1) g2 x
= (f . g1) x (g2 x)
= f (g1 x) (g2 x)
You can try this:
import Control.Arrow
composition = f . (g1 &&& g2)
(&&&) turns g1 :: a -> b and g2 :: a -> c into g1 &&& g2 :: a -> (b, c). Then you can apply normal composition.

Coq: Defining a special function

I want to define a function f w/ 2 explicit arguments. The types of the arguments and value of f are applications of some g. Suppose the arguments' types are g x y and g z w. The tricky part is that f's value must depend on the unifiability of x and z. Below is a naive attempt at defining f that fails. How should I tackle this?
Inductive A := a | a0 | fa.
Inductive B := b | b0.
Parameter C: Type.
Parameter g: A -> B -> C.
Parameter CT:> C -> Type.
Parameter gab: g a b.
Parameter ga0b: g a0 b.
Definition f {x y z w}(n: g x y)(m: g z w) :=
ltac:(match x with z => exact (g z b) | _ => exact (g fa b) end).
Compute f gab ga0b. (*= g fa b: C*)
Compute f gab gab. (*! = g fa b: C !*)
f's value must depend on the unifiability of x and z
It is impossible to write such a definition. Suppose you could write a function that could tell whether or not two natural numbers unified, call it unify_nat : nat -> nat -> bool. Consider now the functions
F := fun x y : nat => if unify_nat (x + y) (y + x) then True else False
G := fun x y : nat => if unify_nat (x + y) (x + y) then True else False
We can prove, because addition is commutative, that forall x y, F x y = G x y. But then unify_nat (x + y) (y + x) must return true, even though x + y and y + x do not unify.
There are two things you can do: (1) you can ask not if the terms unify, but if they are propositionally equal; and (2) you can write a notation, or an alias, which is like syntactic sugar for a definition.
1.
The command Scheme Equality will generate an equality decision function for most inductive types:
Scheme Equality for A.
Definition f {x y z w}(n: g x y)(m: g z w) :=
if A_beq x z then g z b else g fa b.
Compute f gab ga0b. (*= g fa b: C*)
Compute f gab gab. (*= g a b: C*)
2.
We can create evars with open_constr:(_) and use unification to infer the types of n and m:
Ltac f_tac n m :=
let x := open_constr:(_) in
let y := open_constr:(_) in
let z := open_constr:(_) in
let w := open_constr:(_) in
let n := constr:(n : g x y) in
let m := constr:(m : g z w) in
match x with z => exact (g z b) | _ => exact (g fa b) end.
Notation f n m := (ltac:(f_tac n m)) (only parsing).
Compute f gab ga0b. (*= g fa b: C*)
Compute f gab gab. (*= g a b: C*)

Confused about functional composition in Haskell

I know that (.) f g x = f (g x). Suppose f has type Int -> Int, g has type Int -> Int -> Int. Now let h be defined by h x y = f (g x y). Which of the following statements are true and why (why not)?
a. h = f . g
b. h x = f . (g x)
c. h x y = (f . g) x y
Supposedly, only b. is true, while the others are false. I would think a. and b. are equivalent... a. is saying two functions are equal. Two functions are equal only iff when I add an argument to the end of both sides, it will still be equal. So I get h x = f . g x. Now (.) is an operator, so functional application takes precedence over it, so f . g x = f . (g x), which is b.
This looks like a homework, so I won't give the answer of which one is correct.
You consider a and b as identical incorrectly. If f . g is applied to x, you get (from the definition of (.))
(f . g) x = f (g x)
But b is f . (g x), which doesn't expand to f (g x). If you follow b through using the definition of (.), you will see the sense in the comments of the others.
Function composition's initial definition is a bit confusing, so I'll write it a different way:
f . g = \a -> f (g a)
This means that f . g returns a function which first applies the argument to g, then applies the result of that to f. This is also clear in the type signature:
(.) :: (b -> c) -> (a -> b) -> (a -> c)
Now for your function h, it has a type of something like h :: a -> a -> a. Remember that -> is right-associative, so the type could be written as h :: a -> (a -> a). Essentially, h :: a -> b, though this type would cause an error because b and a are uninferrable. (.) will only allow one argument to be applied to the first function, so:
-- One could write,
h x y = f (g x y)
-- But One could also write
h x = f . g x
-- Or, more clearly:
h x = (f) . (g x)
This is because Haskell functions are curried, so we can apply some arguments to g without fully evaluating it.
If we imagine what would happen if we applied (.) visually, then simplify, we can see how it works:
h x = \a -> f ((g x) a)
h x = \a -> f (g x a)
h x a = f (g x a)
So yes, b is the answer. This is because (.) only allows one argument to be applied to the first function before moving to the next.
Now you're job can be tackling the other incorrect solutions by simplifying as I have. It's not too difficult.